Political Reservations and Women’s Entrepreneurship in India - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2013)
This paper quantifies the link between the timing of state-level implementations of political reservations for women in India with the role of women in India's manufacturing sector. It does not find evidence that overall employment of women in manufacturing increased after the reforms. However, the analysis finds significant evidence that more women-owned establishments were created in the unorganized/informal sector. These establishments were concentrated in industries where women entrepreneurs have been traditionally active and the entry was mainly found among household-based establishments. This heightened entrepreneurship does not appear linked to changes in reporting, better access to government contracts and business, or improved financing environments. One interpretation of these results is that the implementation of the political reservations inspired more women to open establishments, and they did so at a small establishment scale in industries where they had experience and/or the support networks of other women.